The Relationship of Regular Exercise and Diet with Degenerative Diseases Among the Residents of Housing Kanjuruhan Asri, Malang City - Sapto Adi, Galih; Gesang Kinanti, Rias; Olivia, Andiana (KnE Life Sciences, 2021)
This study aims to find out both partially and simultaneously the relationship of Exercise Regularity (X1 ) and Diet (X2 ) with the Incidence of Degenerative Diseases (Y) among the residents of Housing Kanjuruhan Asri, Malang City. The study uses a purposive proportional random sampling survey method. The instrument of the study was a questionnaire that has previously been validated by the Pearson’s Product Moment validity test and Spearman Brown’s reliability test (Split Half). Data were analysed using the Spearman’s Rank and Multiple Correlation techniques. The results showed that Regularity of Exercise (X1 ) had a correlation coefficient of 0.881 and Diet (X2 ) a correlation coefficient of 0.963 with the Degenerative Disease Incidence (Y). Also, Regularity of Exercise (X1 ) and Diet (X2 ) had a simultaneous relationship with degenerative disease incidence (Y) with a correlation coefficient of 0.966. The results of the Coefficient of Determination (R2 ) test of 0.932 explained the contribution of the influence of the variables Exercise Regularity (X1 ) and Diet (X2 ) to the variable Degenerative Disease Incidence (Y) of 93.2%; which is quite high. Therefore, it is concluded that there is a significant relationship both partially and simultaneously between Exercise Regularity (X1 ) and Diet (X2 ), and the Incidence of Degenerative Diseases (Y) among the residents of Housing Kanjuruhan Asri, Malang City. Keywords: regularity sport, diet, degenerative diseases, questionnaire